The Art of Documenting Scientific Knowledge: A Case Study of Two South African Grade 12 Science Teachers - Ramulumo, Moleboheng; Mokiwa, Hamza Omari (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
The purpose of this article was to investigate and present effective strategies and innovative approaches that science teachers could employ to comprehensively and accurately document students' scientific knowledge. The study focused on addressing the challenges that arose during the documentation process and aimed to help teachers overcome these obstacles to ensure precise and thorough documentation of their students' scientific understanding. Two science teachers specializing in Physical Sciences and Life Sciences were interviewed through a phenomenological approach to gain insights into their perspectives and experiences. The findings demonstrated that incorporating multiple tasks, such as practical investigations, concept maps, mind maps, research projects, and group discussions, enhanced students' comprehension, and engagement with scientific concepts. These strategies accommodated diverse learning styles and abilities, fostering inclusivity, and facilitating a comprehensive learning experience. The study also highlighted the challenges posed by limited resources and restricted access to laboratory equipment, proposing the adoption of innovative assessment methods, including virtual simulations, to overcome these limitations. The implications of the study underscored the importance of comprehensive teacher training, resource allocation, collaborative approaches, integration of technology, and curriculum design aligned with the documentation of scientific knowledge. The ultimate objective of this article was to contribute to the enhancement of science education and promote scientific literacy by offering practical insights for science teachers in effectively documenting students' scientific knowledge.